In Utero Fetal Programming and Its Impact on Health in Adulthood (2012)
Adverse events during intrauterine life may program organ growth and favor disease later in life. This is the usually called 'Barker's hypothesis'. Increasing evidence suggests that conditions like vascular disease, hypertension, metabolic syndrome, and type 2 diabetes mellitus are programmed during the early stages of fetal development and become manifest in late stages of life, when there is an added impact of lifestyle and other conventional acquired environmental risk factors that interact with genetic factors. The aim of this review was to provide additional, updated evidence to support the association between intrauterine fetal health and increased prevalence of chronic non-communicable diseases in adulthood. Various potential cellular and molecular mechanisms proposed to be related to the above hypothesis are discussed, including endothelial function, oxidative stress, insulin resistance, and mitochondrial function. © 2011 SEEN.